El legado de kapuscinski a los futuros y actuales periodistas (2021)
Ryzsard Kapuscinski was one of the main journalists and masters of this activity. His recent death leaves a very big empty place among the teachers and journalists currently working, because he was always a witness of the human pain, and a critic of the social injustice done by the powerful people. Last year three teachers compared the concepts of the ideal journalist that Kapuscinski defended with the teacher practices and the “ supposed” that some people had about the formation of the journalists in Pereira, the present paper is derived from this work.